A tailwind for climate policy - Friedemann Müller (Stiftung Wissenschaft und Politik (SWP), 2004)
There is new hope for climate policy, and at least three events have provided a reason for this hope: The Russian ratification of the Kyoto Protocol enables it to come into force on February 16, 2005. With Tony Blair's G-8 initiative, announced in a forceful speech on September 14, 2004, a heavyweight in international politics gave his full support to the goals of an extended climate policy for the first time. Finally, on January 1, 2004, the European emissions trading system will come into force, a premiere that is receiving worldwide attention. Now accompanying measures are needed to take advantage of the present boost. The Tenth Session of the Conference of Parties (December 6-17, 2004) in Buenos Aires offers the first chance. This momentum, however, must also be used at the G-8 Summit next year (July 6-8, 2005) to establish a basis for climate policy that extends beyond Kyoto. (SWP Comments / SWP)
Keywords: 320